SIKAP WANITA KARIR TERHADAP TANGGUNG JAWAB PENDIDIKAN ANAK DALAM KELUARGA DI KABUPATEN BANYUMAS - Suparjo Suparjo (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2009)
The modern .iystem of life gives women effort to participate in public domain and even there are several occupations which are identified as profession for the women. In relation to the gender, especially with regard to married women in handling domestic tasks, it is very important to elaborate whether or not such social development actually supports gender equity. This is the big question that will be answered by this research. To do so, this research is only focused on how married female employees in Banyumas regency take part in handling education for their children. At the end, this research led to three conclusions. First, married female employees in Banyumas regency tend to correspond with feminist paint of view or at least functionalist point of view. None of them supported patriarchal point of view. However, the second conclusion indicated that such attitude did not undermine their responsibility to take part in educating their children. The third conclusion found that the main reason for that is they enjoy performing their double tasks, both as mothers and employees.